Synthesis, antimicrobial activity and molecular docking studies of novel hydantoin derivatives as potential phospholipase A2 inhibitors - Cynthia E. Theodore; G. Sivaiah; S.B. Benaka Prasad; K. Yogesh Kumar; M.S. Raghu; Fahd Alharethy; M.K. Prashanth; Byong-Hun Jeon (Chemical Physics Impact, 2023)
This work presents the synthesis, characterization and evaluation of a series of new multifunctional N-substituted hydantoin derivatives for their antibacterial and antifungal activity. Elemental analysis, 1H NMR, 13C NMR, and mass spectroscopy were used to confirm the newly synthesized compounds' structure. The antibacterial and antifungal properties of each synthesized molecule were examined. The examined compounds showed significant to moderate antimicrobial activity against the tested Gram-positive, Gram-negative, and fungal strains with MIC values ranging from 10.3 to 84.2 µM. Compounds 22 (MIC: 11.7–13.5 µM) and 25 (MIC: 10.2–11.9 µM) demonstrated an impressive MIC value against the tested bacterial and fungal strains when compared to the reference medications fluconazole (MIC: 11.7–14.5 µM) and streptomycin (MIC: 14.5 µM), which are broad-spectrum antibiotics and antifungal agents, respectively. Additionally, all of the compounds were tested for their ability to inhibit the phospholipase A2 (PLA2) enzyme, with the IC50 values ranging from 8.53 to 65.14 µM. When compared to the reference drug ursolic acid (IC50: 12.58 µM), compounds 22 (IC50: 10.27 µM) and 25 (IC50: 8.53 µM) were shown to be the most potent PLA2 inhibiting compounds in this series. The findings of the Molecule description with Drug-Likeness Prediction demonstrated that all the compounds are in a linear correlation with Lipinski's rule of five, demonstrating good drug-likeness qualities. The inhibitory effects of the most potent compounds (18, 19, 22 and 25) against the target PLA2 protein (PDB ID: 2H4C) were explained by molecular docking studies. The molecular docking results were in good accord with the experimental findings, and as these compounds had superior binding affinities within the active pocket, they may be classified as potent inhibitors of specific targets.